pH-Sensitive and Charge-Reversal Polymeric Nanoplatform Enhanced Photothermal/Photodynamic Synergistic Therapy for Breast Cancer - Wang, Wenyan; Li, Zimu; Nie, Xiaozhong; Zeng, Wenfeng; Zhang, Yi; Deng, Yimin; Chen, Hongzhong; Zeng, Xiaowei; Ma, Hualin; Zheng, Yi; Gao, Nansha (Frontiers in Bioengineering and Biotechnology, 2022)
As reported, breast cancer is one of the most commonly malignancies in females and has overtaken lung cancer as the most commonly diagnosed cancer worldwide by 2020. Currently, phototherapy is a promising anti-tumor therapy due to lower side effects, less invasion, and less cost. However, its application in cancer therapeutics is limited by the incomplete therapeutic effect caused by low drug penetration and monotherapy. Herein, we built a charge-reversal nanoplatform (Ce6-PLGA-PDA-PAH-DMMA NPs), including polydopamine (PDA) and chlorin e6 (Ce6) for enhancing photothermal/photodynamic synergistic therapy. The PAH-DMMA charge reversal layer enabled Ce6-PLGA-PDA-PAH-DMMA NPs to have long blood circulation at the normal physiological environment and to successfully realize charge reversal under the weakly acidic tumor microenvironment, improving cellular uptake. Besides, in vitro tests demonstrated that Ce6-PLGA-PDA-PAH-DMMA NPs had high photothermal conversion and greater anti-tumor activity than no charge-reversal nanoparticles, which overcame the limited tumor therapeutic efficacy of PTT or PDT alone. Overall, the design of pH-responsive and charge-reversal nanoparticles (Ce6-PLGA-PDA-PAH-DMMA NPs) provided a promising approach for synergistic PTT/PDT therapy against breast cancer.